Domestic boiling and salad preparation habits affect glucosinolate degradation in red cabbage (Brassica oleracea var. capitata f. rubra). (15th August 2020) - Hanschen, Franziska S.
Highlights: Domestic preparation techniques affected glucosinolate degradation in red cabbage. Acid addition in salad preparation of red cabbage increased isothiocyanates. Acidic boiling led to increased glucosinolate boiling and nitrile formation. Short neutral boiling of "blue" cabbage increased isothiocyanate release. Abstract: Red cabbage contains glucosinolates, precursors to health-promoting isothiocyanates. However, raw cabbage often releases mainly epithionitriles and nitriles from glucosinolates. To increase isothiocyanate formation, the effect of acid usage in the preparation of red cabbage was evaluated. Moreover, the effects of the chosen boiling method (acidic boiled red cabbage versus neutral boiled blue cabbage) on glucosinolate degradation were investigated using UHPLC-DAD-ToF-MS and GC–MS. The addition of vinegar significantly increased isothiocyanate formation of cabbage salad from 0.09 to 0.21 µmol/g fresh weight, while lemon juice only slightly increased isothiocyanate formation. Acidic boiled red cabbage degraded glucosinolates and increased nitrile formation, while in neutral boiled blue cabbage, glucosinolates were stable. However, shortly boiled blue cabbage (5 min) had the highest isothiocyanate levels (0.08 µmol/g fresh weight). Thus, for a diet rich in isothiocyanates it is recommended to acidify raw cabbage salads and prepare shortly boiled blue cabbage instead of red cabbage.